Tolkien's Phonoprint in Character Names Throughout His Invented Languages. (3rd July 2018) - Wilcox, Brad; Brown, Bruce L.; Baker-Smemoe, Wendy; Morrison, Timothy G.
Abstract : J. R. R. Tolkien claimed to create names based on sound symbolism and invented languages. Previous studies revealed that Tolkien had his own phonoprint (tendency to use the same phonemes repeatedly for character names) regardless of his claims that they reflected different language origins. However, this research examined phonemes and syllables rather than names as whole units. This study compared 183 names from Tolkien's works and 100 names from the nineteenth Century US Census. The name recognition software linked names with known languages or provided a "generic" category when no match was found. Results showed no significant differences between the generic listings when language groups were compared. It seems Tolkien successfully created unique names, but could not escape his own phonoprint among the generic names. When looking at names from non-generic responses, it appears Tolkien was able to differentiate into three language groups, but not with the precision he claimed.